Integrating Behavioral Reasoning Theory and Two-Step Clustering to Determine Farmer Typology in the Adoption of New High-Yielding Rice Varieties Protani - Akhmad Rizqul Karim; Indah Widyarini; Rifki Andi Novia; Sarno (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
The low adoption rate of the Protani new high-yielding rice variety (HYV) indicates that farmers' decisions are driven not only by technical factors but also by behavioral considerations and risk perceptions. Research on HYV adoption generally relies on conventional socioeconomic approaches and seldom integrates behavioral frameworks and farmer typology segmentation. This study aims to identify farmer typologies using a Two-Step Clustering approach and analyze differences in variables within the Behavioral Reasoning Theory (BRT) framework and demographic characteristics across the identified groups. Employing a quantitative descriptive design, a field survey using a purposive sampling technique was conducted with 51 Protani rice farmers in Bojanegara Village, Purbalingga Regency, Central Java Province, from September to October 2024. Data were analyzed using the Two-Step Clustering algorithm in R-Studio based on BRT psychological factors as indicators, which was subsequently validated through Principal Component Analysis (PCA) visualization and ANOVA testing. The results reveal three distinct adopter typologies: progressive, pragmatic, and skeptical. The BRT variables significantly differentiate the three groups. The progressive group is dominated by older, experienced farmers who are highly receptive to innovation; the pragmatic group exhibits the highest resistance due to comprehensive risk calculations; whereas the skeptical group possesses high adoption intentions but is hindered by farming constraints. Formal education levels show no significant differences across the typologies. This study underscores that agricultural extension and innovation dissemination strategies must be tailored to farmers' behavioral characteristics to enhance the efficacy of HYV adoption.